The effect of microelements supplementation on beta-oxidation activity in healthy and type 1 diabetic rats - Kuryl, Tomasz; Debski, Bogdan; Martiník, Karel (Central European Journal of Public Health, 2008)
Diabetes mellitus type 1 disease changes the activity of fatty acid degradation as compared to healthy animals. Supplementation in vitro with microelements chromium Cr3+ and selenium Se4+ and Se2- in non-toxic ([96.15 pmol (5 ppm) for chromium and 6.33 micromol (0.5 ppm) for selenium] concentrations strongly stimulates the activity of this process in diabetic rats. In healthy animals only chromium Cr3+ in concentration of 96.15 micromol (5 ppm) stimulated beta-oxidation activity in lymphocytes. It may indicate the beneficial effect of supplementation of the diet with microelements, chromium Cr3 and selenium Se4+ or Se2- at concentrations as low as 100 micromol for chromium and 6 micromol for selenium, respectively.
Keywords: financování organizované; streptozocin; Animals; experimentální diabetes mellitus; mastné kyseliny; lymfocyty; hmotnostní přírůstek; Rats, Wistar; stopové prvky; Chromium Compounds; Fatty Acids; Weight Gain; Dietary Supplements; Trace Elements; Blood Glucose; Selenium Compounds; potravní doplňky; Insulin; sloučeniny selenu; Financing, Organized; Diabetes Mellitus, Type 1; oxidace-redukce; Male; Oxidation-Reduction; krysa rodu Rattus; Lymphocytes; Streptozocin; sloučeniny chromu; zvířata; mužské pohlaví; inzulin; krevní glukóza; Rats; diabetes mellitus 1. typu; potkani Wistar; Diabetes Mellitus, Experimental